Antibody mediated rejection. Evidence based medicine. What is the current evidence? - Menezes,Maria do Mar (2020)
Antibody mediated rejection (ABMR) is a major cause of kidney graft loss. The ideal treatment remains unknown, is not standardized and there is little evidence to support the use of any specific therapy. This paper aims to reflect on the current state of this challenging diagnosis, either active or chronic active ABMR, and its treatment options. The current treatments encompass plasma exchange, steroids, intravenous immunoglobulin, rituximab, bortezomib, eculizumab, C1 inhibitors, IL 6 inhibitors and IgG-degrading enzyme of Streptococcus pyogenes among others. We will try to analyze the main studies that sustain or reject the current and future use of these techniques and drugs.